Current knowledge and practice regarding syntocinon for caesarean sections in a department of anaesthesiology - De Jager, Marike (My University, 2017)
Background: More than 166 000 women die annually from obstetric haemorrhage, with uterine atony being the most common causative factor (3). More than 50% of these deaths occur in Sub-Saharan Africa (4, 5). Synthetic oxytocin is integral in the prevention and management of postoperative post partum haemorrhage (PPH) and therefore it is essential for anaesthesiologists to have an adequate knowledge of this drug. Aim: The aim of the study was to describe the current knowledge and practise of the anaesthetists in the department of Anaesthesiology at the University of Witwatersrand (Wits), regarding Syntocinon® during caesarean section under spinal anaesthesia. Method: A validated questionnaire was distributed to anaesthetists working at Wits during departmental academic meetings in April 2015. Results: The results of the study showed that 60% of the participating anaesthetists had inadequate knowledge of IV Syntocinon® and that practice varied widely and was based on individual participants’ preference and was not consistent with international guidelines or protocols. Conclusion: Urgent staff education and implementation of a standardised practice guideline and protocol regarding usage and dosing of IV Syntocinon® is needed to prevent poor maternal outcomes and poor service delivery.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology April 2017
Keywords: Cesarean Section Syntocinon